Employment protection legislation, multinational firms and innovation - Rachel Griffith; Gareth Macartney (Institute for Fiscal Studies (IFS), 2010)
The theoretical effects of labour regulations such as employment protection legislation (EPL) on innovation is ambiguous, and empirical evidence has thus far been inconclusive. EPL increases job security and the greater enforceability of job contracts may increase worker investment in innovative activity. On the other hand EPL increases adjustment costs faced by firms, and this may lead to under-investment in activities that are likely to require adjustment, including technologically advanced innovation. In this paper we find empirical evidence that both effects are at work - multinational enterprises locate more innovative activity in countries with high EPL, however they locate more technologically advanced innovation in countries with low EPL.
Keywords: D21; F23; O31; J24; 330; Innovation; employment protection; multinational firm location; Arbeitsplatzsicherung; Personalkosten; Betriebliche Investitionspolitik; Innovation; Wettbewerb; Betriebliche Standortwahl; Multinationales Unternehmen; Theorie